Transparency as a Principle of Employment Agreement in the Perspective of Islamic Law - Musofiana, Ida; Indarti, Indarti (UNISSULA Semarang, 2023)
Humans as social creatures cannot be separated from relationships with other humans. In social relations, it is inseparable from the existence of an agreement. The implementation of the agreement does not always run smoothly, there are obstacles in the form of default or there are parties who cannot fulfill their achievements. The object of this research is that the principle of openness is needed in implementing work agreements. Therefore, Muslims are required to carry out muamalah activities on the basis of Islamic law and study them in detail regarding the principles of cooperation The purpose of this research is to analyze what are the principles in the agreement. The method used in the research with the study of laws and regulations and rules in Islamic law Al-Qur;an, Al-Hadith and relevant Islamic law rules. The results and important findings in this study found the existence of the principle of sekufu commensurate in the implementation of employment agreements between business actors.